Cinema as a medium for disaster literacy and risk communication in Indonesia - Wuryantari, Benedicta Ayu Indiwara; Kurniadi, Anwar; Subiyanto, Adi (Priviet Social Sciences Journal, 2026)
This study examines the role of cinema and audiovisual media as strategic instruments for strengthening disaster literacy and risk communication in Indonesia through a qualitative Systematic Literature Review (SLR) guided by the PRISMA framework. A total of 25 articles published between 2021 and 2025 were systematically selected from national indexed databases (SINTA and Garuda) and international academic platforms using keywords related to disaster films, educational media, and disaster literacy. The selected literature was analyzed using thematic synthesis and classified into four analytical dimensions: disaster representation, educational and literacy functions, social and psychological impacts, and mitigation and preparedness practices. The findings show that research in this field is largely oriented toward educational and mitigation perspectives, particularly through documentaries, animations, and digital learning media that convey disaster-related information in accessible and persuasive ways. Cinema is also understood as a cultural medium that integrates technical knowledge with emotional and social narratives, supporting the formation of collective awareness, empathy, and community engagement in disaster-prone areas. Audiovisual media further function as dialogical spaces linking formal education, community-based learning, and institutional risk communication strategies with implications for community preparedness and participatory disaster governance. This study contributes to the theoretical understanding of film as a medium of social representation and disaster communication, identifies gaps in long-term behavioral evaluation, and offers practical recommendations for integrating audio-visual media into disaster education and community outreach. Overall, cinema shows strong potential as a sustainable tool for strengthening disaster preparedness and enhancing social resilience in Indonesia.